2017
DOI: 10.1080/02602938.2017.1353586
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the predictive validity of high school grades for academic success in university

Abstract: To refine selective admission models, we investigate which measure of prior achievement has the best predictive validity for academic success in university. We compare the predictive validity of three core high school subjects to the predictive validity of high school grade point average (GPA) for academic achievement in a liberal arts university programme. Predictive validity is compared between the Dutch pre-university (VWO) and the International Baccalaureate (IB) diploma. Moreover, we study how final GPA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 26 publications
1
7
2
1
Order By: Relevance
“…However, the use of the new API yields a better goodness of fit for the obtained models. Indeed, the adjusted R 2 values in the present study range from 0.449 for the Biology degree to 0.727 for the Mathematics degree, which are much higher than the R 2 values obtained in previous research considering factors of merit other than pass/fail outcomes .…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…However, the use of the new API yields a better goodness of fit for the obtained models. Indeed, the adjusted R 2 values in the present study range from 0.449 for the Biology degree to 0.727 for the Mathematics degree, which are much higher than the R 2 values obtained in previous research considering factors of merit other than pass/fail outcomes .…”
Section: Discussioncontrasting
confidence: 85%
“…However, the use of the new API yields a better goodness of fit for the obtained models. Indeed, the adjusted R 2 values in the present study range from 0.449 for the Biology degree to 0.727 for the Mathematics degree, which are much higher than the R 2 values obtained in previous research considering factors of merit other than pass/fail outcomes [11,[17][18][19][20][21]. Gender is commonly included in academic performance studies and, generally, female students are shown to outperform male students in primary, middle and high school.…”
Section: Discussioncontrasting
confidence: 62%
“…There are also several important nuances concerning the predictive validity of grades. Grades from previous education lose their predictive validity in later years of study (Sladek et al 2016;Vulperhorst et al 2018). This supports the notion that high school and the first year of the bachelor's program require mostly lower-order knowledge, whereas the third year of the bachelor's program requires higher-order knowledge (Steenman 2018).…”
Section: Non-cognitivesupporting
confidence: 54%
“…Nonetheless, McKenzie and Schweitzer (2001, 29) mentioned that 'university entry scores need to be interpreted with caution, as they explain less than half of the variance in GPA'. Vulperhorst et al (2018) compared the predictive validity of high school scores on academic success in university between the Dutch pre-university (314 graduates) and the International Baccalaureate (n ¼ 113 graduates) diploma. According to the authors, the most valid high school score to be used for selection procedures in higher education remains unclear, and it seems to depend on the diploma students enter with.…”
Section: Introductionmentioning
confidence: 99%